The Urgency Of Holistic Parenting In Optimising Child Development - Devi Fitria Sandi; Esti Pratiwi Yosin; Masruroh Masruroh (CV. Inara, 2024)
Child growth and development are influenced by the nurturing environment, especially mother-child interactions, parenting style, and family stimulation. parenting style, and family stimulation. Objective of this research is to assess the knowledge and skills of holistic parenting skills performed by parents.This research is qualitative with a literature study approach. Primary data sources were accessed from scientific journals, scientific books, videos, images and other sources that are compatible with this paper. The sources were sorted, analysed and conclusions were drawn.Parenting patterns are associated with the incidence of stunting in toddlers.Parents' knowledge can help them to maximise their efforts to develop their children's character and apply the right parenting parenting. Parents who know about parenting will endeavour to fulfil their children's developmental needs.